Valuation of fisheries management status based on ecosystem approach (EA) in East Simeulue, Aceh - Ratna Mutia Aprilla; Celli Dirgantini; Edy Miswar; Thaib Rizwan; Djamani Rianjuanda; Salmarika Salmarika; Alvi Rahmah; Imelda Agustina; Ratu Sari Mardiah (Depik, 2023)
Fishery management is an activity that must be carried out to achieve sustainable fisheries. Fisheries management using the Ecosystem Approach to Fisheries Management (EAFM) approach is the sustainable use of fishery resources and protection of fish stocks in nature. One of the objectives of fisheries management in social and economic aspects is how fisheries can ensure the socio-economic welfare of the fishing community. Using fishing gear that is not environmentally friendly is one of the triggers for social conflict between fishermen and the uncertain selling price when the peak season of fish impacted the fishermen's economy. Therefore, the purpose of this research is to examine the socio-economic domain indicators from the aspect of EAFM-based coastal and marine resource ecosystem management. This research was conducted from January to February 2021, located in Simeulue District, Sub-District East Simeulue. The data collection method used in the study was interviews and field surveys. The determination of respondents is done by using a gradual sampling technique or stratified random sampling. Data analysis uses an ordinal-based Likert score of 1,2,3 for each indicator, namely the economic domain, fishery household income (RTP), savings ratio, asset ownership, and the social domain, namely stakeholder participation fisheries conflict and the use of local knowledge in fish resource management. Management status in East Simeulue District assessed the aggregate value of the economic domain in the medium category with a score of 48.3. Fishermen still earn less than the minimum wage, while in the social domain, it is in the excellent category with a score of 100 because fishermen, institutions, and related agencies work with each other. Keywords:EAFMEcosystem approachFishery management